Activation of Skeletal Muscle Satellite Cells by a Device Simultaneously Applying High-Intensity Focused Electromagnetic Technology and Novel RF Technology: Fluorescent Microscopy Facilitated Detection of NCAM/CD56 - Halaas, Yael; Duncan, Diane; Bernardy, Jan; Ondrackova, Petra; Dinev, Ivan (Aesthetic surgery journal, 2021)
BACKGROUND: Myosatellite cells are myogenic stem cells that can transform to provide nuclei for existing muscles or generate new muscle fibers as documented after extended exercise programs. OBJECTIVES: The authors investigated whether the simultaneous application of High-Intensity Focused Electromagnetic (HIFEM) and Synchrode radiofrequency (RF) affects the levels of satellite cells similarly as the prolonged exercise does to achieve muscle growth. METHODS: Three 30-minute simultaneous HIFEM and Synchrode RF treatments (once a week) were administered over the abdominal area of 5 Large White swine aged approximately 6 months. All animals were anesthetized during the treatments and biopsy acquisition. Biopsies of muscle tissue were collected at baseline, 4 days, 2 weeks, and 1 month post-treatment. After binding the specific antibodies, the NCAM/CD56 levels, a marker of activated satellite cells, were quantified employing the immunofluorescence microscopy technique with a UV lamp. RESULTS: Examined slices showed a continuous increase in satellite cell levels throughout the study. Four days after the treatment, we observed a 26.1% increase in satellite cells, which increased to 30.2% at 2-week follow-up. Additional histological analysis revealed an increase in the cross-sectional area of muscle fibers and the signs of newly formed fibers of small diameters at 2 weeks after the treatment. No damage to muscle tissue and no adverse effects related to the treatment were observed. CONCLUSIONS: The findings indicate that the simultaneous application of HIFEM and novel Synchrode RF treatment can initiate differentiation of satellite cells to support the growth of existing muscles and, presumably, even the formation of new myofibers.
Keywords: molekuly buněčné adheze nervové; Technology; Microscopy, Fluorescence; Swine; Radio Waves; fluorescenční mikroskopie; kosterní svaly; Animals; technologie; rádiové vlny; satelitní buňky kosterního svalu; Neural Cell Adhesion Molecules; zvířata; prasata; Muscle, Skeletal; Satellite Cells, Skeletal Muscle